Market analysis of medicinal products with nimesulide - Dykun, Darya; Tarapon, Kateryna; Tryhubchak, Oksana (The Ukrainian Scientific Medical Youth Journal, 2022)
nimesulide-containing medicinal products are the most popular non-steroidal anti-inflammatory drugs which have been widely used in practice for many years. This active substance belongs to selective cyclooxygenase 2 inhibitors is a powerful pain reliever characterized by a rapid therapeutic effect compared to other pain relievers. Despite the contradictory literature data of the last decades regarding the use of nimesulide due to its hepatotoxic effect, nimesulide medicine remain a priority in the treatment of patients with pain syndrome of various genesis all over the world. Currently, nimesulide is produced in the world in various dosage forms. Some studies in recent years have proved its antitumor effect which has led to the appearance of new specific forms with nimesulide such as microgranules, microspheres, nanoparticles with targeted delivery. Therefore, the purpose of the investigation was to analyze Ukrainian pharmaceutical market of products with the nimesulide active substance by dosage forms, manufacturers; to establish the quality composition of original and generic drugs. The objects of the study were medicinal products containing nimesulide registered in Ukraine. The study was performed by analyzing of register data, using methods of grouping, comparison, graphic analysis, and generalization. In the work an analysis of medicines with nimesulide by dosage form and manufacturers was carried out. The excipients composition of reference drugs for nimesulide granules for oral suspension was also investigated. It was established that 32 medicines with nimesulide are registered in Ukraine, including 28 mono-preparations. A significant part of medicinal products with nimesulide are solid dosage forms, namely tablets (47 %) or granules for oral suspension (22 %) which contain 100 mg of nimesulide. It was established that there are no nimesulide in the form of prolonged-release tablets on the domestic market. Nimesulide drug products of foreign producers are dominant (59.38 %), India has a leading position (50 %). Granules are mainly produced by foreign manufacturers that confirms the feasibility of developing a domestic generic product. The original product is Aulin, granules for oral suspension, “Angelini Pharma”, Czech Republic. Differences in the qualitative composition of excipients of the original and generic products which present on the Ukrainian market were observed. The composition of products more often includes sucrose as filler, сetomacrogol 1000, liquid glucose spray-dried, maltodextrin, sodium saccharin, anhydrous citric acid, orange flavoring, corn starch, or Aerosil 200. As follows, the feasibility of development of domestic medicinal product in the form of prolonged-release tablets and granules was confirmed; the original product of nimesulide granules for oral suspension was determined and the qualitative composition of the reference drugs was established.